1996
DOI: 10.1006/cbir.1996.0062
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Synthesis and Utilization in Cultured Human Osteoblasts

Abstract: This study describes the adhesion of human osteoblasts, cultured in vitro, to proteins of the extracellular matrix, the biosynthesis of integrins, their topography and organization in focal contacts. The adhesion of osteoblasts to laminin, type I collagen, vitronectin and fibronectin was 77-100%, in 2 h and at 55 nM substrata concentration, and it was accompanied by spreading of the cells. Adhesion to fibronectin (FN), laminin (LN) and type I collagen (COL) was inhibited by antibodies to the beta 1 integrin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…RGD peptides also significantly reduced fibronectinmediated attachment, but to a lesser extent than RGD blockade of CBE-mediated attachment (27% for FN vs. 98% for CBE). The modest effect of RGD peptides on fibronectin-mediated attachment is in agreement with several other studies, and suggests that attachment of DU145 cells to fibronectin can occur via non-RGD motifs [20][21][22].…”
Section: Discussionsupporting
confidence: 91%
“…RGD peptides also significantly reduced fibronectinmediated attachment, but to a lesser extent than RGD blockade of CBE-mediated attachment (27% for FN vs. 98% for CBE). The modest effect of RGD peptides on fibronectin-mediated attachment is in agreement with several other studies, and suggests that attachment of DU145 cells to fibronectin can occur via non-RGD motifs [20][21][22].…”
Section: Discussionsupporting
confidence: 91%
“…Collagen VI is necessary for collagen I production in osteoblast like cells (Harumiya et al, 2002) and interlukin-4-dependent mineralization of human periosteal cells (Ishibashi et al, 1999). Likewise fibronectin, which supports attachment and spreading of hMSC and osteoblasts (Salasznyk et al, 2004b;Ogura et al, 2004;Pistone et al, 1996), is secreted by osteoblasts early in development, and may act to help organize the osteoid matrix by binding to collagen I in mature bone tissue (Nordahl et al, 1995). Damsky and colleagues have demonstrated that osteoblast/fibronectin interactions supply a necessary regulatory signal essential for osteogenic gene expression, with fibronectin possibly playing a role in the recruitment of osteoblast precursor cells (Globus et al, 1995;Moursi et al, 1996;Globus et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…␣v␤3 is involved in migration on vitronectin whereas ␣v␤5 plays a role in spreading on the same substrate in human monocytes [De Nichilo and Burns 1993]. Moreover, ␣v␤3 and ␣v␤5 have been shown to distribute differentially with ␣v␤3 at the focal adhesion sites whereas ␣v␤5 more diffusely distributed when human osteoblasts are cultured in serum, presumably on vitronectin [Pistone et al, 1996].…”
Section: Discussionmentioning
confidence: 99%